2019
DOI: 10.1177/2331216519847413
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Effects of Adjusting Hearing-Aid Gain by Means of a Machine-Learning Approach Based on Individual User Preference

Abstract: This study investigated a method to adjust hearing-aid gain by use of a machine-learning algorithm that estimates the optimal setting of gain parameters based on user preference indicated in an iterative paired-comparison procedure. Twenty hearing-impaired participants completed this procedure for 12 different sound scenarios. During the adjustment procedure, their task was to indicate a preference based on one of three sound attributes: Basic Audio Quality, Listening Comfort, or Speech Clarity. In a double-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…There are alternative strategies involving such things as paired comparison and machine learning. Some of these strategies extend to other factors such as the criteria used by listeners and the properties of the sound input during self-adjustment (e.g., Jensen et al, 2019). Empirical comparisons of methods for self-fitting and postfitting selfreadjustment are clearly needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are alternative strategies involving such things as paired comparison and machine learning. Some of these strategies extend to other factors such as the criteria used by listeners and the properties of the sound input during self-adjustment (e.g., Jensen et al, 2019). Empirical comparisons of methods for self-fitting and postfitting selfreadjustment are clearly needed.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of user adjustment of amplification has been demonstrated using a variety of protocols that incorporate changes of frequency response (Boothroyd & Mackersie, 2017;Dreschler et al, 2008;Jensen et al, 2019;Keidser & Convery, 2018;Keidser et al, 2008;Mackersie et al, 2019;Nelson et al, 2018). Groupmean user-adjusted frequency responses are generally close to threshold-based prescribed targets (typically within 5 dB), but substantial individual differences have been observed (Jensen et al, 2019;Keidser & Convery, 2018;Mackersie et al, 2019;Nelson et al, 2018;Punch et al, 1994). In addition, Nelson et al (2018) reported that on average, speech recognition outcomes of self-adjusted responses were not significantly different from those using the current version of the National Acoustics Laboratories prescription for Non-Linear hearing aids (NAL-NL2; Keidser et al, 2011).…”
mentioning
confidence: 99%
“…Advances are being made in provisions of technologies to assist HA users with calibrating their own HA, for example via smartphones i.e. Pasta et al (2019) andSøgaard Jensen et al (2019), and indeed many modern HAs are sold along with proprietary smartphone apps which enable some extent of personalisation. These services enable HA users to change their HA calibrations whilst in a "live" situation, so as to correct their hearing as they go about different everyday activities.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made to produce smartphone technology to help HA users to train their HA through personalising their settings in different environments. Emerging techniques using smartphone apps connected to Bluetooth enabled HAs have been recently described (Aldaz, Puria, & Leifer, 2016;Pasta, Petersen, Jensen, & Larsen, 2019;Søgaard Jensen, Hau, Bagger Nielsen, Bundgaard Nielsen, & Vase Legarth, 2019), in which user-preference is incorporated into an ongoing calibration process. These studies reported positive findings relating to different aspects of the hearing experience for conditions in which HAs had been optimized by the user.…”
mentioning
confidence: 99%
“…This approach worked well for determining the similarity between images (Houlsby et al, 2013) and has also been used in auditory applications. For example, GPs have been used to search for the optimal setting of a hearing aid (Jensen et al, 2019;Nielsen et al, 2014), and for determining audiograms (Cox & de Vries, 2015;Schlittenlacher et al, 2018a;Song et al, 2015), equal-loudness contours (Schlittenlacher & Moore, 2020), and psychometric functions (Song et al, 2017). Other BAL approaches, often using parametric models but also maximizing mutual information or something similar, have been used to determine equal-loudness contours (Shen et al, 2018) or the edge frequency of a dead region (Schlittenlacher et al, 2018b).…”
mentioning
confidence: 99%